Specification for solderable tin or tin-lead coated wires for component terminations (BSI, 1991)
Electric wires, Electric terminals, Solderability testing, Tin, Test specimens, Thickness, Determination of content, Test equipment, Bend testing, Soldered connectors, Marking, Atomic absorption spectrophotometry, Chemical analysis and testing, Reverse-bend tests, Coated materials, Electric conductors, Metal coatings, Dimensions, Packaging, Elongation values